Finite element analysis on reinforced concrete column with transverse openings - Tan, Keen Hong (2017)
In construction, openings and holes are drilled to place ducts and pipes for accommodation of services such as electricity, water supply, telecommunication, air conditioning and so on. The presence of such openings may influence the performance of reinforced concrete column, especially from the aspect of load carrying capacity. This study mainly focus on the deflection and crack patterns of reinforced concrete column having opening with different sizes and opening in different locations. Study was conducted on columns specimens with rectangular cross-section of 300 mm x 300 mm and 3800 mm height. All columns specimens were reinforced with longitudinal reinforcement of 4H 20, transverse reinforcement of shear links with 6 mm diameter and 250 mm spacing. Finite element analysis was conducted to study the behaviour of the reinforced concrete column using ANSYS software. The load is applied until the failure of the column models. The result shows that the deflection or the deformation of the control column is the highest and the deflection of the column decreases when the opening size of column increases. The deflection is the highest when opening located in the center of column span. For cracks pattern, more cracks are formed when the opening size increases and when the opening located closer to the applied load.